The immediate effect of patellar tendon strap on weight-bearing asymmetry during squatting in patients with unilateral knee osteoarthritis: A pilot study - DEMİRBÜKEN, İLKŞAN (SAGE PUBLICATIONS LTD, 2016)
Background: Knee osteoarthritis has commonly been associated with a symptom of pain resulting in an inter-limb weight-bearing asymmetry during functional tasks. Patellar tendon strap is one of the non-pharmacologic interventions to alleviate knee pain. Objectives: To investigate the immediate effect of a patellar tendon strap on weight-bearing asymmetry during squatting in people with unilateral knee osteoarthritis. Study design: Cross-sectional study. Methods: Ten patients with unilateral knee osteoarthritis and 10 healthy subjects were included in the study. Weight-bearing asymmetry of patients was assessed using a weight-bearing squat test during squatting at 30 degrees and 60 degrees both with and without patellar tendon strap. Pain intensity was assessed during squatting in unstrapped and strapped conditions with Visual Analog Scale. Results: The decrease in weight-bearing asymmetry values immediately after wearing patellar tendon strap during 30 degrees (p=0.006) and 60 degrees (p=0.011) of squatting tests was significantly higher in knee osteoarthritis patients than in healthy subjects. Reported pain intensity was similar in unstrapped and strapped conditions (p=0.066). Conclusion: The results of this study showed improved inter-limb weight-bearing symmetry during squatting. Further research with larger sample sizes investigating the effect of patellar tendon strap on weight-bearing asymmetry during functional activities in people with knee osteoarthritis is warranted. Clinical relevance Patellar tendon straps (easily fit and cheap unlike knee braces) had more improvements in inter-limb weight-bearing symmetry during squatting in people with knee osteoarthritis compared to healthy subjects. This study is a new insight for future studies to investigate clinical benefits of wearing patellar tendon straps in this population.
Keywords: Knee osteoarthritis; weight-bearing asymmetry; squatting; patellar tendon strap; PATELLOFEMORAL PAIN; FUNCTIONAL MOBILITY; MANAGEMENT; RECOMMENDATIONS; INFRAPATELLAR; IMPAIRMENT; MOVEMENT; TRIALS